Evaluation of flavourings potentially used in a heated tobacco product: Chemical analysis, in vitro mutagenicity, genotoxicity, cytotoxicity and in vitro tumour promoting activity. (August 2018) - Crooks, Ian; Neilson, Louise; Scott, Ken; Reynolds, Lorna; Oke, Tobi; Forster, Mark; Meredith, Clive; McAdam, Kevin; Proctor, Chris
Abstract: We designed a novel tobacco-heating product (THP) that heats tobacco to release nicotine and aerosolised components, such as glycerol and tobacco volatiles from a tobacco rod (Neostik). Heating tobacco significantly reduces levels of combustion-derived toxicants in the aerosol compared to cigarette smoke. This study was conducted to determine whether the inclusion of potential flavourings in the THP would add to the levels of toxicants in the emissions or alter in vitro responses. Levels of measured toxicants were similar in the flavoured and unflavoured Neostik emissions and significantly less than emissions from the reference cigarette, 3R4F. No mutagenicity was observed with the Neostiks in the Ames test or in the mouse lymphoma assay. There was evidence of a weak genotoxic response in the in vitro micronucleus test using V79 cells from both Neostiks and these responses were less than 3R4F. They did not show tumour-promoting potential in the Bhas 42 cell transformation assay and were not cytotoxic in the Neutral Red uptake assay. 3R4F elicited toxic responses in all assays at significantly lower concentrations. The addition of flavourings to the Neostik tested did not alter the chemical profile of THP emissions or change in vitro responses relative to the unflavoured Neostik. Highlights: Tobacco-heating products, with and without flavourings and 3R4F chemical emissions were measured and tested in vitro. Emissions of the tobacco heating devices were comparable and less than 3R4F. 3R4F was mutagenic, genotoxic, cytotoxic and demonstrated tumour promoting potential. TPM from the two THPs showed weak activity in the in vitro micronucleus assay only.